Eksplorasi Kemampuan Berpikir Aljabar Siswa Sekolah Dasar dalam Menyelesaikan Soal Manipulasi Numerik - Annisa Nur Fauziyah; Masduki (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2023)
This study aims to explore the algebraic thinking skills of elementary school students in solving math problems. The method used is descriptive qualitative. The subjects of the study were 129 fifth grade elementary school students from two private schools in Surakarta, Central Java, Indonesia. In this paper, the researcher limits the analysis of the algebraic thinking skills of students who have low abilities. The data collection technique used an instrument in the form of 15 algebraic thinking test questions which included components of numerical manipulation, modeling, and functions. This paper presents an analysis of the four numerical manipulation component problems. The results showed that students with low algebraic thinking skills used stacked addition, subtraction and multiplication strategies in solving numerical manipulation component problems even though the steps used were not precise. In addition, students also experience errors in solving problems. In other words, the ability of students is one of the factors that affect the ability to think algebra.